Quantum spin-liquid state in a triangular lattice of S = 1/2 spin trimers in KBa3Ca4Cu3V7O28 - Dr Andrej Zorko; Dr Panchanana Khuntia; Miss Tina Arh; Dr James Lord (ISIS Facility, 2019)
Geometrical frustration conspiring with quantum fluctuations in low-dimensional antiferromagnets has been demonstrated over the past years to lead to novel quantum states in condensed matter. Quantum spin liquids (QSL) on two-dimensional lattices are particularly intriguing, as they are extremely elusive and therefore poorly understood. Triangular lattice antiferromagnets are candidates for a QSL ground state if perturbations to the nearest-neighbour isotropic interactions are present. Here we focus on a novel triangular lattice of Cu2+ trimers in KBa3Ca4Cu3V7O28, which might host a QSL ground state, as all bulk measurement performed down to 50 mK so far failed to detect magnetic ordering. Therefore, we propose a muSR study in a sub-kelvin temperature range to unambiguously confirm the spin-liquid conjecture in KBa3Ca4Cu3V7O28 and to characterize its low-lying magnetic excitations.
Keywords: STFC ISIS Neutron and Muon Data